Exploring the multifunctionality in metal–organic framework materials: how do the stilbenedicarboxylate and imidazolyl ligands tune the characteristics of coordination polymers?. (29th March 2018) - Barsukova, Marina O.; Sapchenko, Sergey A.; Kovalenko, Konstantin A.; Samsonenko, Denis G.; Potapov, Andrei S.; Dybtsev, Danil N.; Fedin, Vladimir P.
Abstract : A synergistic effect causes MOF materials to demonstrate excellent iodine vapor retention and luminescence properties. Abstract : Six isoreticular metal–organic frameworks (MOFs) based on zinc, cadmium and cobalt ions, 4, 4′-stilbenedicarboxylic acid and the flexible ligands 1, 4-bis(imidazol-1-yl)butane and 1, 6-bis(imidazol-1-yl)hexane were prepared. The synergistic effect coming from the assembly of stilbenedicarboxylate and imidazolyl ligands led to multifunctional materials with excellent photoluminescence and good sorption capacity for carbon dioxide and iodine vapor.